ChemInform Abstract: Ullmann Homocoupling Catalyzed by Gold Nanoparticles in Water and Ionic Liquid. Issue 12 (14th March 2013) - Monopoli, Antonio; Cotugno, Pietro; Palazzo, Gerardo; Ditaranto, Nicoletta; Mariano, Bruno; Cioffi, Nicola; Ciminale, Francesco; Nacci, Angelo
Abstract The gold nanoparticle catalyst is prepared in situ from gold(III) acetate with glucose as reducing agent.